2018
DOI: 10.1002/suco.201700133
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lightweight aggregate, freezing–thawing procedure and air entraining agent on freezing–thawing damage

Abstract: This article presents the results of a study dealing with the concrete resistance to repeated cycles of freezing and thawing of nonair entrained, fine lightweight aggregate (LWA) and air‐entrained concrete when tested in accordance with ASTM C 666, procedures A and B. The water‐to‐binder ratios (w/b) of the mixtures ranged from 0.25 to 0.35, and the percentage of cement replacement by silica fume were 7% on a weight basis and constant throughout study. Binder dosage was 500 kg/m3 and constant. LWA was pumice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 36 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…It was observed that the compressive strengths of EPA10, EPA20, and EPA30 reduced 3.97, 9.40, and 18.55% for 28 days and 5.33, 9.21, and 16.64% for 90 days, respectively. A significant decrease in the compressive strength occurred for the higher amount expanded perlite . For instance, the compressive strength of C was 68.74 MPa while the EPA30’s compressive strength was 57.30 MPa for 90 days.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It was observed that the compressive strengths of EPA10, EPA20, and EPA30 reduced 3.97, 9.40, and 18.55% for 28 days and 5.33, 9.21, and 16.64% for 90 days, respectively. A significant decrease in the compressive strength occurred for the higher amount expanded perlite . For instance, the compressive strength of C was 68.74 MPa while the EPA30’s compressive strength was 57.30 MPa for 90 days.…”
Section: Resultsmentioning
confidence: 95%
“…A significant decrease in the compressive strength occurred for the higher amount expanded perlite. 36,37 For instance, the compressive strength of C was 68.74 MPa while the EPA30's compressive strength was 57.30 MPa for 90 days. According to Table 4, the unit weight of fresh concrete is decreased with increasing the EPA content.…”
Section: Linear Autogenous Shrinkagementioning
confidence: 98%
“…The strength development was accelerated, and the concretes also showed a low surface scaling of 82 g/m 2 when subjected to 56 freeze-thaw cycles in a 3% NaCl solution. Concrete without admixtures showed surface scaling of 11,851 g/m 2 [25,37,38].…”
Section: Opc-based Concretesmentioning
confidence: 99%
“…Freezing‐and‐thawing damage often occurs in the water‐level fluctuation zone or on the downstream side of water projects, and freezing‐and‐thawing damage is especially serious for thin‐walled concrete structures, such as aqueducts, gate piers, slabs, and buttress dams. Therefore, it is important to study the frost resistance durability of concrete structures in water engineering applications 2 …”
Section: Introductionmentioning
confidence: 99%